Long-run expectations of households - Christoph Breunig; Iuliia Grabova; Peter Haan; Felix Weinhardt; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
The rational expectations assumption, e.g. in life-cycle models and portfolio-choice models, prescribes agents to have model-consistent beliefs and to avoid systematic prediction errors. In reality, justi cation and identification of expectations are nontrivial. One way to solve this problem is to elicit expectations collecting survey data. We utilize the German SOEP Innovation Sample to analyze short-run and long-run expectations of households in three different domains: stock market, labor market and housing market. Our main contribution to the existing literature is that we study expectations about price developments over longer periods, which is of central relevance since many important economic decisions of households concern the long run. Previous studies have mainly focused on short-run or medium-run expectations. We document that while expectations about wages are similar to historical values, the long-run expectations about the developments of the stock market index and about house prices are strongly pessimistic. In the case of the stock market, respondents expect only a small percentage of historical growth. We also observe substantial heterogeneity of expectations by socio-economic background.
Keywords: D63; H23; I24; I38; J22; J31; 330; Long-run expectations; Biased beliefs; Returns to education